2020
DOI: 10.1007/s12274-020-3207-9
|View full text |Cite|
|
Sign up to set email alerts
|

Exciton recycling via InP quantum dot funnels for luminescent solar concentrators

Abstract: Luminescent solar concentrators (LSC) absorb large-area solar radiation and guide down-converted emission to solar cells for electricity production. Quantum dots (QDs) have been widely engineered at device and quantum dot levels for LSCs. Here, we demonstrate cascaded energy transfer and exciton recycling at nanoassembly level for LSCs. The graded structure composed of different sized toxic-heavy-metal-free InP/ZnS core/shell QDs incorporated on copper doped InP QDs, facilitating exciton routing toward narrow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Lanthanide ions have several interesting properties as potential sensitizers, such as ladder-like electronic states and long radiative lifetimes (10 μs–10 ms), which can promote luminescence conversion. However, their progress as downshifters is limited since Ln 3+ ions (e.g., Yb 3+ , Er 3+ , Tm 3+ , Nd 3+ and Ho 3+ ) have narrow absorption widths as well as very small absorption cross sections due to their electric-dipole-forbidden 4f→4f transitions. , Although traditional semiconductor nanocrystals (NCs) such as CdSe, , InP, and Ag 2 Se have a high absorption cross section and can be used as host materials, their covalently bonded rigid lattices complicate the doping process with lanthanide ions. , Instead, halide perovskites are ideal for substitutional doping due to the softness and strong ionicity of their lattice, and additionally they offer very high absorption cross sections. ,, Various reports have shown that in lead halide perovskites a downshifted luminescence in the visible and infrared spectral range can be achieved through doping with divalent cations (for instance, Cd 2+ , Mn 2+ ), , trivalent cations (Ln 3+ ), ,, or a combination thereof . Yet, the toxicity and stability issues of lead-based perovskites are a strong drive toward alternative metal halides, and several Pb-free double perovskites (e.g., Cs 2 AgInCl 6 , Cs 2 AgBiX 6 (X = Cl, Br), , and Cs 3 Bi 2 Br 9 ) have been synthesized and tested as hosts.…”
Section: Synthesis Of Cs3mnbr5 and Csmnbr3 Ncsmentioning
confidence: 99%
“…Lanthanide ions have several interesting properties as potential sensitizers, such as ladder-like electronic states and long radiative lifetimes (10 μs–10 ms), which can promote luminescence conversion. However, their progress as downshifters is limited since Ln 3+ ions (e.g., Yb 3+ , Er 3+ , Tm 3+ , Nd 3+ and Ho 3+ ) have narrow absorption widths as well as very small absorption cross sections due to their electric-dipole-forbidden 4f→4f transitions. , Although traditional semiconductor nanocrystals (NCs) such as CdSe, , InP, and Ag 2 Se have a high absorption cross section and can be used as host materials, their covalently bonded rigid lattices complicate the doping process with lanthanide ions. , Instead, halide perovskites are ideal for substitutional doping due to the softness and strong ionicity of their lattice, and additionally they offer very high absorption cross sections. ,, Various reports have shown that in lead halide perovskites a downshifted luminescence in the visible and infrared spectral range can be achieved through doping with divalent cations (for instance, Cd 2+ , Mn 2+ ), , trivalent cations (Ln 3+ ), ,, or a combination thereof . Yet, the toxicity and stability issues of lead-based perovskites are a strong drive toward alternative metal halides, and several Pb-free double perovskites (e.g., Cs 2 AgInCl 6 , Cs 2 AgBiX 6 (X = Cl, Br), , and Cs 3 Bi 2 Br 9 ) have been synthesized and tested as hosts.…”
Section: Synthesis Of Cs3mnbr5 and Csmnbr3 Ncsmentioning
confidence: 99%
“…However, the nonradiative surface states in QD solid-state films cannot be perfectly passivated even with excess ligand treatments, which leads to a lower PLQY in solid-state integrated devices . For example, excitons in QDs can cause Förster-type resonance energy transfer to nonradiative exciton states in neighboring QDs, which can be suppressed by engineering the shell thickness and Auger recombination . Alternatively, QDs in liquids keep their efficiency without any interaction with other QDs and efficiency-decreasing host matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, European Union research on exposure of nanomaterials, NANOMICEX, provides the guidelines for future development of less-toxic, environmentally friendly nanoparticles for commercial and biomedical applications, for which InP-based ones hold a great promise. Although InP QDs in either core or core/shell structures were extensively studied in several different fields including solar cells, fluorescent imaging markers, bioconjugated sensors, detectors, luminescent solar concentrators, and LEDs, ,, their potential in neural interfaces remained unrevealed. On the other hand, their biocompatibility for both in vitro and in vivo studies was carefully studied in the literature, which they were used as optical probes for imaging and as nanocarriers for drug delivery applications …”
Section: Quantum Dot Systems For Neural Stimulationmentioning
confidence: 99%